METHODS OF PROCESSING ANALOG PARAMETERS OF AIRCRAFT FLIGHT INFORMATION - Savchenko, Alina; Neporozhniy, Gennady; Pivovarov, Oleksandr (Science-based technologies, 2023)
Modern systems of aircraft objective control make it possible to accumulate a whole mass of information obtained during a certain cycle of operation, which makes it possible to increase the flight safety. It is important to determine the main control parameters and methods of processing the data obtained. The article discusses the main analog parameters for objective flight control and modern methods of their processing. The information technology of statistical data processing is considered, which involves determining the necessary nomenclature of objective information, determining the frequency of data collection and the accuracy of measurement channels, the technology of hardware acquisition, exchange and storage of data, performing statistical data processing and forecasting the state of the control object. It is noted that the accuracy of the measured parameters is always subjective and corresponds to the established tolerances. Parameters always change their values over time under the influence of various factors, creating a general picture of "white noise". Isolation of useful signals ("state signs") from general "noise" requires the recognition of some standard for groups of researched objects (subjects). The number of processed "signs" is determined by the principle of sufficiency, with the desire for "minimalism". In order to fulfill the requirements of ICAO and integration into a unified flight safety control system, with the agreement on common airspace with the EU (Open Skies Program), it is necessary to create (improve) a modern flight control system based on new physical and digital principles of flight data processing using high-speed transmission technologies.